Indonesia-China agreement and Jakarta's inconsistency on the South China sea issue - Basundoro, Alfin Febrian (2025)
Indonesian President Prabowo Subianto’s agreement with China on joint maritime development in the South China Sea raises concerns over Indonesia’s commitment to national sovereignty and international law. While economically beneficial, it risks legitimising China’s claim in the South China Sea, straining relations within ASEAN, threatening local livelihoods, and undermining Indonesia’s regional reputation and longstanding foreign policy principles.